IHSAN KEPADA KEDUA ORANG TUA: TINJAUAN TAFSIR SOSIAL KONTEMPORER - Muhammad Shodiq (STAI ALHIKMAH Jakarta, 2020)
Abstract This study aims to reveal the interpretation of the Koran about doing good (ihsan) to parents which is explicitly mentioned 13 (thirteen) times, and which is mentioned 7 (seven) times directly after Allah swt invites and calls on people to tauhid and thanksgiving. to him. In social practice, how a person has good character to both parents is revealed in this study with Tafsir al-Amthal fi Tafsir Kitabillah al-Munzal by Makarim Syairazi as the primary source. This Interpretasion is a contemporary social interpretation. Meanwhile, the secondary data in this study are other authoritative and relevant social interpretation works. The findings of this research are that the meaning of ihsan applies to both parents in the Koran is in the form of monotheism that must be put forward to accompany the worship of both parents. Ihsan is absolute covering all goodness, including the category whether the religious status of both parents is Muslim or infidel. be civilized when both parents are weak, old and old, who desperately need protection and affection from their children. Be gentle and respectful when communicating with him. Be tawadhu 'and pray for them when they are still alive or not. Always ask Allah for an easy way to serve both parents. Abstrak Penelitian ini bertujuan untuk mengungkap penafsiran Al-Quran tentang berbuat baik (ihsan) kepada orang tua yang secara tersurat disebutkan sebanyak 13 (tiga belas) kali, dan yang 7 (tujuh) kali disebut langsung setelah Allah swt mengajak dan menyerukan umat kepada tauhid dan sukur kepada-Nya. Dalam praktik sosial, bagaimana seseorang berakhlaq baik kepada kedua orang tua diungkap dalam penelitian ini dengan Tafsir al-Amthal fi Tafsir Kitabillah al-Munzal karya Makarim Syairazi sebagai sumber primer. Tafsir Al-Amthal merupakan tafsir yang bercorak sosial kontemporer. Sedang data sekunder dalam penelitian ini adalah karya tafsir sosial lainnya yang otoritatif dan relevan dengan kajian ini. Temuan penelitin ini adalah bahwa makna berlaku ihsan kepada kedua orang tua dalam Al-Quran adalah berupa tauhid yang harus dikedapankan yang mengiringi kebaktian terhadap kedua orang tua. Ihsan bersifat mutlak meliputi semua kebaikan termasuk kategori apakah status agama kedua orang tua muslim ataupun kafir. bersikap beradab ketika kedua orang tua dalam masa lemah, renta dan tua yang sangat membutuhkan perlindungan dan kasih sayang dari anaknya. Bersuara lembut dan hormat ketika berkomunikasi dengannya. Bersikap tawadhu’ dan mendoakan mereka ketika masih hidup maupun telah tiada. Selalu memohon kepada Allah untuk di anugerahi jalan mudah untuk berkhidmat kepada kedua orang tua.